Economic Growth and Financial Management for SMEs: Perspectives on Community Economic Business Sustainability - Suriani, Seri; Nur, Indrayani; Fatmawati, Fatmawati; Baharuddin, Sitti Mujahida (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
Natural resource-based economic growth impacts increasing the productivity of small and medium enterprises (SMEs) in Wajo Regency. This study aims to analyze: (1) Economic growth and financial management performance work as determinants of increasing the productivity of small and medium enterprises (SMEs), (2) The direct and indirect effects of financial management, technology utilization, business diversification, and product innovation, on business productivity economics and business sustainability of SMEs, dan (3) Financial management strategy and productivity of SMEs in supporting economic growth. This study uses a combination of qualitative-quantitative approaches sequentially—data obtained through observation, in-depth interviews, surveys, and documentation. The results of the study indicate that the optimization of financial management performance and the effectiveness and efficiency of the utilization of business capital impact increasing the productivity of SMEs. Furthermore, financial management, technology utilization, business diversification, and product innovation directly affect the productivity of SME economic enterprises with a determination coefficient of 60.58%. The increase in SMEs' business productivity directly and indirectly affects their business sustainability, with a determination coefficient of 67.73%. This study recommends financial management based on the effectiveness and efficiency of the utilization of business capital coupled with the use of technology, business diversification, and product innovation, which are essential parts that need to be considered in the formulation of economic development policies in the framework of encouraging increased productivity and business sustainability of SMEs in Wajo Regency, South Sulawesi, Indonesia.